PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK CHANGE OF PAIRSUNTUK MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL-SOAL SUB POKOK BAHASAN LUAS TRAPESIUM KELAS VII A SMP NEGERI 7 JEMBER TAHUN AJARAN 2012/2013 - MS, Mega Nirmalasari; Susanto, S; Sri Lestari, Nurcholif Diah (Department of Mathematics Education , University of Jember, 2013)
Abstract.Cooperative learning by using change of pairs technique is a learning model which gives chancefor thestudentstoask andstrengthentheir answerfor the exercises.This research implementscooperative learning by using change of pairs technique to reduce student’s errorin solving problems of area of trapezoid. The subject of the research is grade VII A students of SMP Negeri 7 Jember. The type of this research is a Classroom Action Research (CAR). The data collection methods used in this research are observation, documentation, interview, and test. The result shows that the errors are decreasing; misused data decrease from 50% to 0%; distorted theorem or definition decrease from 59,38% to 12,5%; technical errors decrease from 61,25% to 9,34%; and other error decrease from 27,5% to 1,25%. The result also shows that the activity of the students and the teacher in teaching and learning process are increasing. KeyWords:changeofpairs technique, student's error, area of trapezoid